STUDIES ON RABBIT LYMPHOCYTES IN VITRO : VIII. THE RELATIONSHIP BETWEEN HETEROZYGOSITY AND HOMOZYGOSITY OF LYMPHOCYTE DONOR AND PER CENT BLAST TRANSFORMATION INDUCED BY ANTIALLOTYPE SERA - Sell, Stewart (The Rockefeller University Press, 1968)
Rabbit antisera to immunoglobulin allotype Ab4 will stimulate a maximum of 77% (mean ± SEM = 39.78 ± 4.8) blast transformation of Ab4Ab4 homozygous lymphocytes in vitro and a maximum of 39% (mean ± SEM = 19.77 ± 1.6) blast transformation of heterozygous Ab4Ab5 lymphocytes. Similarly anti-Ab5 sera will induce a maximum of 82% (mean ± SEM = 50.83 ± 7.0) blast transformation of Ab5Ab5 homozygous lymphocytes in vitro and a, maximum of 42% (mean ± SEM = 16.1 ± 1.6) blast transformation of heterozygous Ab4Ab5 lymphocytes. Thus, the lymphocytes of an allotypically heterozygous rabbit appear to be selected to produce or express only one of the two genetically supplied allotypic determinants controlled by the "b" locus. A similar conclusion has been made in regard to allotypic expression by immunoglobulin-producing plasma cells. Previous data indicate that each lymphocyte carries or expresses more than one immunoglobulin group specificity (IgG, IgA, IgM) while each plasma cell carries only one. One possible interpretation of these data is that, while the production of immunoglobulin groups and allotypic specificities are under similar control in both the lymphocyte and the plasma cell, the lymphocyte produces immunoglobulin that remains in or attached to itself and the plasma cell produces immunoglobulins that are secreted rapidly.